Proximal Relining with Custom Made Double Branch Aortic Arch Graft to treat a type Ia Endoleak after Zone 2 Branched TEVAR - Simona Sica; Jonathan Sobocinski (EJVES Vascular Forum)
Objective: Thoracic endovascular aortic repair (TEVAR) including a branch or fenestration offers a less invasive alternative to open surgery in the treatment of aortic arch pathologies. Nevertheless, the occurrence of a proximal type I endoleak (EL) in this specific setting may be particularly challenging to fix. This study presents the case of a type Ia endoleak after a zone 2 single branched TEVAR that was successfully treated with a proximal endovascular relining using a custom made double branch aortic arch graft. Case: A 74 year old male presented with a 70 mm thoracic aortic aneurysm and a type Ia EL 7 years after a zone 2 TEVAR including a retrograde left subclavian artery branch. After multidisciplinary discussion, the patient underwent a hybrid repair with left carotid subclavian bypass and a custom made double branch aortic arch graft to extend proximal sealing into zone 0. The device that was used featured two antegrade inner branches for the brachiocephalic trunk and left common carotid artery. Post-operatively, the patient recovered well without neurological deficit. Follow-up imaging at three months confirmed patency of the supra-aortic trunks and favourable aortic remodelling without any residual endoleak. Conclusion: This case suggests that proximal endovascular relining in zone 0 with a custom made double branch aortic arch for treating type Ia endoleak following left subclavian artery branch endograft is feasible and effective in experienced aortic centres.